A Rapid Assessment of Road Crashes in Uganda: Notes from the Field - Abel Wilson Walekhwa; Francis Mulolo; Carla Achiro; Mary Nantongo; Brenda Nakazibwe; Monica Musenero Masanza (Dr. Sulaiman Al Habib Medical Journal)
Background Road crashes continue to persist on Ugandan roads despite the government's commendable efforts over many years. This study sought to explore the persistent causes of road crashes, suggest recommendations and evaluate the costs incurred by the government for treating accident victims. Methods A rapid cross-sectional study involving both quantitative and qualitative study approaches was performed. Desk reviews and six key informant interviews were conducted with traffic police officers and hospital administrators. Traffic road accident data were abstracted from the Uganda Police Force database for the period of January 2021 to February 2022, to ascertain the magnitude of the problem and its causes. Results The causes of road accidents are mainly caused by to human error, weather and the poor state of some roads. The government spends reasonable amounts of money in treating accident victims, at USD 245–3590, yet the funds could instead be used to promote socio-economic development in communities. Conclusion Road crashes continue to occur in Uganda, mainly because of human error. We recommend amelioration of the identified causes of road traffic crashes to save lives and conserve limited public resources.